Assessment and analysis of heavy metal pollution in key production areas of Gastrodia elata in Yunnan, China - Qian, Xixi; Luo, Yu; Yang, Honglei; Wang, Jinghui; Zhang, Huimin; Shi, Huineng; Li, Qi; Song, Zhanhua; Hao, Bing; Fan, Wei (Frontiers in Environmental Science, 2025)
IntroductionAs a newly recognized medicinal and edible Chinese herbal medicine, the safety of Gastrodia elata has garnered significant attention. Yunnan Province is the main production area of G. elata in China, but there is a lack of systematic assessments of the distribution patterns of heavy metals in the soil-plant system and their associated human health risks.MethodsThis study evaluated the pollution status of five heavy metals—cadmium (Cd), arsenic (As), lead (Pb), mercury (Hg), and copper (Cu)—in the surface soil (0–20 cm) and G. elata tubers across four major planting areas: Kunming (KM), Zhaotong (ZT), Lijiang (LJ) and Tengchong (TC) in Yunnan Province. The concentrations of heavy metals in soil and G. elata tubers were determined using inductively coupled plasma mass spectrometry (ICP-MS) and atomic fluorescence spectrometry (AFS). The pollution status of heavy metals in soil was evaluated using the single pollution index (Pi), comprehensive pollution index (PN), potential ecological risk index (PERI), and enrichment factor (EF). The bioconcentration factor (BCF) was applied to assess the accumulation capacity of heavy metals in the plants, while the target hazard quotient (HQ) and total hazard index (HI) were used to evaluate the human health risks associated with heavy metals in G. elata tubers.Results and discussionThe findings revealed that the surface soils in the sampling areas were acidic, with total nitrogen (TN), total potassium (TK), soil organic matter (SOM), and cation exchange capacity (CEC) reaching abundant levels, while total phosphorus (TP) was relatively low. The pollution levels of the five heavy metals were ranked as Hg > Cd > Cu > As > Pb, with Hg, Cd, and Cu identified as severely polluted. The potential ecological risk assessment indicated a moderate risk, with ZT showing the highest comprehensive pollution level and ecological risk. The enrichment capacity of heavy metals in soil was ranked as Hg > Cd > As > Pb > Cu, while in G. elata tubers it was Cd > Cu > Pb > As. However, there was no significant risk to human health. Correlation analysis indicated that soil Cd and Pb were significantly positively correlated with their respective heavy metal content in G. elata (P < 0.05/P < 0.001). This study provides a scientific basis for controlling soil heavy metal pollution in G. elata planting areas and for assessing the safety of Chinese herbal medicines.